Oil and Gas Budget Revenues in Russia after Crisis in 2015 - Mikhaylov, Alexey (International Journal of Energy Economics and Policy, 2019)
The paper propose the energy market crisis impact on the Russian budget revenues in 2015. We develop the model to forecast the impact of oil prices on budget revenues in Russia. The practical significance of this work lies in the structuring of existing knowledge on oil crisis impact on the Russian budget. Brent crude oil prices were in the range of 115-79 dollars per barrel in 2014. The cyclical strengthening of US dollar and political factors have led to an increase in supply in the oil market by more than 20%. In 2015, we saw a decline in oil prices below $ 40 per barrel. The strengthening of the United States dollar was a major factor in the decline, as it was in the middle of 2001, when the price fell by about a one third before starting a long-term sharp increase. Keywords: oil price forecasting, budget revenues, oil and gas impact. JEL Classifications: E37, F20, G15. DOI: https://doi.org/10.32479/ijeep.6635